Spatial analysis of cement production and consumption in Turkey - Cem Beygo; Goksenin Cakmak (European Regional Science Association (ERSA), 1998)
After 1950?s, the rapid urbanization of Turkey stimulated the production and consumption of cement and the number of cement factories increased since then. In addition, construction of highways, bridges, dams and industrialization also contribute to the consumption of cement. Construction industry became a locomotif of the economy of the country and cement industry is the most element of the construction industry. This study analyzes the growth of population and urbanization according to new provinces and regions between 1960-1990. Further, the growth of the number of cement factories ,and production is illustrated in the provinces and the regions within the same period. Then, the relationships between the growth of cement production and consumption and urbanization of population is analyzed by the use of multiple regression analysis at the regional and national level.
Keywords: 330